the Phenomenon that Influenced the Development of Cool Japan in Indonesia - Fitri Fitri; Aditya Prayoga; Ayu Alfi Syahrina; Nadya Salma Salsabila (Journal of Social Research, 2022)
Background: As is well known that Japan has many unique cultures that can attract people from other countries.   Objective: The goal is to spread Japanese culture through promotion in the creative industry sector to all corners of the world. What Cool Japan wants to achieve is to gain influence from other countries and maintain its status as a cultural superpower country (Tao, 2018).   Methods: This research uses descriptive research method. This method can describe the results of research in a narrative manner to something that is being studied.   Results: the results of research in a narrative of something that is being researched. This research begins with collecting data and information related to the object of research as a basis.   Conslusion: Japan which is one of the countries that has the main strength in the form of many types of Japanese culture which at this time already has the status as a cultural superpower. From the development of existing culture, Japan has a desire to commercialize its culture and dominate the world culture market through traditional culture and popular culture. In 2011 through the Cool Japan Initiative, the popularity of Japanese culture in various countries was exploited by the government by making policies to support their cultural industries.